2005
DOI: 10.1152/japplphysiol.00916.2004
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the preoptic area and anterior hypothalamus by tetrodotoxin alters thermoregulatory functions in exercising rats

Abstract: We have previously demonstrated a functional role of the preoptic area and anterior hypothalamus (PO/AH) in thermoregulation in freely moving rats at various temperature conditions by using microdialysis and biotelemetry methods. In the present study, we perfused tetrodotoxin (TTX) solution into the PO/AH to investigate whether this manipulation can modify thermoregulation in exercising rats. Male Wistar rats were trained for 3 wk by treadmill running. Body core temperature (Tb), heart rate (HR), and tail skin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(39 citation statements)
references
References 47 publications
1
38
0
Order By: Relevance
“…It is important to point out that POA/AH cell groups project to the sympathetic outflow of the tail artery involved in heat loss in the rat (38), producing tail vasodilation when the POA is warmed (19,21,48). In addition, it has recently been shown that inhibition of the POA/AH by local infusion of tetrodotoxin impairs heat loss in running rats (16). A variety of studies have suggested that SFO and other adjacent areas are critical for the central actions of ANG II (7,14) and that SFO afferent communication with paraventricular nucleus utilizes ANG II as a neurotransmitter within this hypothalamic region (25).…”
Section: Discussionmentioning
confidence: 99%
“…It is important to point out that POA/AH cell groups project to the sympathetic outflow of the tail artery involved in heat loss in the rat (38), producing tail vasodilation when the POA is warmed (19,21,48). In addition, it has recently been shown that inhibition of the POA/AH by local infusion of tetrodotoxin impairs heat loss in running rats (16). A variety of studies have suggested that SFO and other adjacent areas are critical for the central actions of ANG II (7,14) and that SFO afferent communication with paraventricular nucleus utilizes ANG II as a neurotransmitter within this hypothalamic region (25).…”
Section: Discussionmentioning
confidence: 99%
“…This notion is supported by a previous study showing that disruption of the preoptic nucleus and anterior nucleus, located in the medial region of the hypothalamus near the PVH and VMH, increases body temperature on exercise. 9 Furthermore, insufficient function of b-endorphin decreased water intake, possibly leading to dehydration and hyperthermia. We, therefore, speculated that hypothalamic dysfunction was responsible for the hyperthermia.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, various studies provide evidence that central dopamine activation plays an important role in thermoregulatory mechanisms; this leads to heat loss and body temperature reduction by inducing central temperature set-point adjustments and increasing heat dissipation through skin vasodilation (Balthazar et al, 2010;Barros et al, 2004;Chaperon et al, 2003;Nunes et al, 1991;Varty & Higgins, 1998). Nevertheless, there is evidence that an increase in dopamine levels in the preoptic area/anterior hypothalamus is followed by hyperthermic responses during exercise (Balthazar et al, 2009(Balthazar et al, , 2010Hasegawa et al 2005Hasegawa et al , 2008Watson et al, 2005). Watson et al (2005) reported that bupropion, despite enabling subjects to maintain a greater time-trial power output while in the heat, led to a higher body temperature.…”
Section: Dopaminementioning
confidence: 99%
“…In contrast, lower heat storage, which attenuates the exercise-induced hyperthermia as a result of stimulation of the central cholinergic system, is closely associated with decreased serotonin levels in the preoptic area at the moment of fatigue (A. G. Rodrigues et al, 2009). Central dopamine metabolism is also enhanced during exercise (Balthazar et al, 2009;Foley & Fleshner, 2008;Hasegawa et al, 2005), and its interaction with serotonin has been linked with high rates of body heating and precipitation of fatigue (Foley & Fleshner, 2008;Meeusen et al, 2007). A combination of effects is induced by central angiotensinergic blockade, which leads to a higher serotonin/dopamine ratio within the hypothalamus at fatigue that correlates directly with the body heating rate and indirectly with the exercise time to fatigue .…”
Section: Predictors Of Fatigue: Static and Dynamic Perspectivesmentioning
confidence: 99%